Optimization of groove geometry for single phase water flow inside horizontal tubes : a numerical study - Urkut, Ahmet Furkan (My University, 2022)
Bu tez çalışmasında, farklı yiv şekillerine (dairesel, üçgen ve kare) sahip yivli boruların Nusselt sayısı, basınç düşüşü, sürtünme faktörü, termal-hidrolik performansı ve entropi üretim oranları numerik olarak incelenmiş ve düz boru ile karşılaştırılmıştır. Daha yüksek ısı transferi ve termal-hidrolik performansa sahip optimum yiv geometrisinin elde edilmesi amaçlanmıştır. Simülasyonlar, laminer ve türbülanslı bölgeler için sırasıyla 400 ile 2000 ve 5000 ile 9000 arasında değişen Reynolds sayısı için sabit ısı akısı koşulları altında gerçekleştirilmiştir. Analizler için 8 mm çapında ve 1 m uzunluğunda yatay yivli boru modelleri kullanılmış ve akışkan olarak su tercih edilmiştir. Dairesel, üçgen ve kare yivli borularda laminer bölgede düz boruya göre Nusselt sayısının sırasıyla %218, %180 ve %140'a kadar arttığı gözlemlenirken, türbülanslı bölgede Nusselt sayısının dairesel, üçgen ve kare yivli borularda düz boruya kıyasla sırasıyla %29, %7.5 ve %3.4’e kadar arttığı görülmüştür. Sonuçlar, dairesel yivli borunun hem laminer hem de türbülanslı bölgelerde en yüksek ısı transferi performansına sahip olduğunu göstermiştir. Isı transferi performansını daha da iyileştirmek için 3, 4, 5 ve 6 mm olarak farklı hatve uzunluklarına sahip dairesel yivli boru modelleri nümerik olarak incelenmiştir. 3 mm hatve uzunluğuna sahip modelin, biraz daha yüksek sürtünme faktörü ve entropi üretim hızına rağmen diğer modellere göre daha üstün ısı transferi ve termal-hidrolik performansa sahip olduğu görülmüştür.

In this thesis study, Nusselt number, pressure drop, friction factor, thermal-hydraulic performance and entropy generation rates of grooved tubes with different groove shapes (circular, triangular and square) were investigated numerically and compared with those of smooth tube. It was aimed to obtain the optimum groove geometry that has greater heat transfer and thermal-hydraulic performance. Simulations were carried out under constant heat flux conditions for Reynolds number varying from 400 to 2000 and 5000 to 9000 for laminar and turbulent regions respectively. 1 m long horizontal grooved tube models with a diameter of 8 mm were used for the analyses and water employed for the fluid domain. It was observed that Nusselt number increases up to 218%, 180% and 140% for circular, triangular and square grooved tubes respectively compared to smooth tube in laminar region while, it was seen that Nusselt number augments up to 29%, 7.5% and 3.4% for circular, triangular and square grooved tubes respectively in comparison with smooth tube in turbulent region. Results showed that circular grooved tube has the highest heat transfer performance in both laminar and turbulent regions. Circular grooved tube models with different pitch lengths as 3, 4, 5 and 6 mm were numerically examined intending to further augment the performance of heat transfer. It was seen that despite its slightly higher friction factor and entropy generation rate, model with 3 mm pitch length has superior heat transfer and thermal-hydraulic performance compared to the other models.
Keywords: basınç düşüşü Grooved tubes; friction factor; groove shape; heat transfer; ısı transferi; Makine mühendisliği; Mechanical engineering; pressure drop; sürtünme faktörü; termal-hidrolik performans; thermal-hydraulic performance; yiv şekli; Yivli borular